Automatic fish feeder / Abdul Nujaidi Mohamed, Syahirul Amir Suhaimi and Ismail Muhamad Asri - Mohamed, Abdul Nujaidi; Suhaimi, Syahirul Amir; Muhamad Asri, Ismail (2016)
This project presents Automatic Fish Feeder using Arduino as a controller. The objectives of this project is to create a device that would automatically feed the fish using Real Time Clock (RTC) that can set the time of the device using current time. Another objective is to alert the owner about the quantity of food in container. The dispensed food will be controlled by a motor which situated under the tank. This project using Light Detecting Resistor (LDR) and RTC as an input, while motor, Liquid Crystal Display (LCD) and Light Emitting Diode (LED) as output. RTC is a computer clock that keeps track of the current time to set real time, LED to show the quantity of food in the tank using red and green colour and LCD to displayed real time. It is operated by the RTC assigning a desired time which will be displayed on the LCD and the fish will be fed three times per day setting by user. The quantity of food will release in 5 seconds that have been programmed by the Arduino. Red LED use as an indicator to show the amount of food in the tank. This device will be installed in aquarium to keep feeding the fish on the right time.